Europe Can Succeed Where America Failed: A Comparative Approach to Gender-Based Violence - Paganetti, Lorenzo (Columbia Journal of Gender and Law, 2023)
Europe Can Succeed Where America Failed: A Comparative Approach to Gender-Based Violence